PENGARUH PROFITABILITAS, LEVERAGE DAN EFISIENSI OPERASI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN RITEL - Hafihz, Annisah; Prameswari, Dolly Adolina (E-Jurnal Akuntansi TSM, 2025)
This study aims to analyze the effect of profitability, leverage, and operational efficiency on financial distress in retail companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Financial distress is a critical financial condition that may lead to bankruptcy, making early identification essential. A quantitative method with a multiple linear regression approach was used. Secondary data were obtained from the annual financial reports of retail companies selected through purposive sampling. The independent variables in this study are Return on Assets (ROA) as a proxy for profitability, Debt to Asset Ratio (DAR) for leverage, and the ratio of operating cash flow to sales for operational efficiency. The results reveal that profitability has a significant negative effect on financial distress, while leverage and operational efficiency show no significant effect. These findings indicate that higher profitability strengthens financial conditions and lowers the risk of distress. This study implies that company management should prioritize net income improvement through effective asset management as a preventive measure against financial distress.